2
$\begingroup$

Let $F$ be a field that doesn't contain a primitive fourth root of unity. Let $L = F(\sqrt a)$ for some $a \in F - F^2$ and let $K=L(\sqrt b)$ for some $b \in L - L^2$.

If we have $N_{L/F}(b) \equiv a\bmod F^{*2}$, prove that:

  1. $K/F$ is a cyclic extension.

  2. $a$ is a sum of two squares in $F$.

$\endgroup$
  • $\begingroup$ What are your thoughts? $\endgroup$ – Zev Chonoles Jun 18 '15 at 9:18
  • $\begingroup$ Well, I know that $[K:F]=4$. Hence $Gal (K/F)$ is either $\mathbb Z_4$ or $\mathbb Z_2 * \mathbb Z_2$. But I don't know if that helps. $\endgroup$ – MathManiac Jun 18 '15 at 9:22
2
$\begingroup$

We need to make the assumption that $F$ is of characteristic different from two, for otherwise both extensions $L/F$ and $K/L$ are inseparable, and there's no hope of getting a Galois extension.


It follows right away that $L/F$ is a cyclic Galois extension of degree two. All the elements $y\in L$ can be written in the form $y=f_1+f_2\sqrt a$ with $f_1,f_2\in F$. The non-trivial $F$-automorphism $\sigma$ of $L$ is given by the recipe $\sigma(f_1+f_2\sqrt a)=f_1-f_2\sqrt a.$

Assume that there exists an element $b=f_1+f_2\sqrt a\in L$ such that $$ N_{L/F}(b)=b\sigma(b)=f_1^2-af_2^2\in a\cdot (F^*)^2.\qquad(*) $$ Because $a\neq0$ $(*)$ implies the existence of $f_3\in F^*$ such that $$ f_1^2-af_2^2=af_3^2\implies f_1^2=a(f_2^2+f_3^2). $$ We first observe that we must have $f_2\neq0$ for otherwise $a=(f_1/f_3)^2\in F^2$.

We must also have $f_2^2+f_3^2\neq0$, for otherwise $f_2^2+f_3^2=0\implies (f_3/f_2)^2=-1$ contradicting the assumption that there are no roots of unity of order four in $F$. Therefore we can write $$ a=\frac{f_1^2}{f_2^2+f_3^2}= \left(\frac{f_1f_2}{f_2^2+f_3^2}\right)^2+\left(\frac{f_1f_3}{f_2^2+f_3^2}\right)^2 $$ as a sum of two squares in $F$.

Next we prove that $K/F$ is Galois. Denote $u=\sqrt{b}$. Equation $(*)$ implies that $ \sigma(b)=af_3^2/b. $ Therefore$$v:=f_3\sqrt{a/b}=f_3\sqrt{a}u^{-1}=\sqrt{\sigma(b)}\in K.\qquad(**)$$ The polynomial $$ \begin{aligned} p(x)&=(x-u)(x+u)(x-v)(x+v)\\ &=(x^2-u^2)(x^2-v^2)\\ &=(x^2-b)(x^2-\sigma(b))\\ &=x^4-(b+\sigma(b))x^2+b\sigma(b)\\ &=x^4-2f_1x^2+a \end{aligned} $$ has its coefficients in $F$. Because $f_2\neq0$ we have $\sqrt a\in F(b)\subseteq F(u)$. The equation $(**)$ then implies that also $v\in F(u)$, so $K=F(u)$ is the splitting field of the separable polynomial $p(x)$ ($b\neq\sigma(b)$, so the roots of $p(x)$ are all simple).

Furthermore, because $K=F(u)$ is of degree four, we can conclude that $p(x)$ is irreducible. This implies that there is an $F$-automorphism $\tau$ of $K$ such that $\tau(u)=v$. Therefore $$\tau(b)=\tau(u^2)=\tau(u)^2=v^2=\sigma(b),$$ so the restriction of $\tau$ to the field $L$ coincides with $\sigma$. Consequently $(**)$ implies that $$ \tau(v)=\tau(f_3\sqrt{a}u^{-1})=f_3\sigma(\sqrt{a})\tau(u)^{-1} =-f_3\sqrt{a}v^{-1}=-f_2\sqrt{a}(f_3\sqrt{a}u^{-1})^{-1}=-u. $$ This implies easily that $\tau$ is of order four proving the missing claim.

$\endgroup$
  • 1
    $\begingroup$ Okay, your definition of a cyclic extension is the same as mine. I don't have the book where I found this question, but I think it should be $b$ instead of $x$ in the given. I am editing the problem statement. $\endgroup$ – MathManiac Jun 18 '15 at 11:24
  • $\begingroup$ Thanks, @PallavGoyal. That should work. Thinking anew... $\endgroup$ – Jyrki Lahtonen Jun 18 '15 at 11:39
  • $\begingroup$ @PallavGoyal: Yup. With that correction everything clicks. All: getting a vibe that this may be a dup. I was too wrapped up in spotting the typo from the original version (and fixing my answer to match the corrected version) that I forgot to check for duplicates. $\endgroup$ – Jyrki Lahtonen Jun 18 '15 at 12:24

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.